Internet use and disruptive behavior in children aged 3, 4 and 5 years from an A.S.A State Garden, Arequipa, 2023 - Condori Espinoza, Edgar Domingo (2024)
The general objective of this study is to determine the relationship between internet use and disruptive behavior in children aged 4 and 5 years old in the state kindergarten of A.S.A. Arequipa 2023. Considering that it is a quantitative, non-experimental correlational study, whose population for this study included 50 boys and girls aged 4 and 5 years, for data collection two questionnaires were processed on the consequences of internet use and on disruptive behavior, which enabled us to assess the variables, the results showed low levels of frequency of internet use in children and low levels of disruptive behavior. In conclusion, it was shown that there is a positive correlation between the variables, i.e., the lower the frequency of internet use, the lower the disruptive behavior in children aged 4 and 5 years in the state kindergarten of A.S.A. Arequipa 2023.